External Debt and Capital Flight in Sub-Saharan Africa. (International Monetary Fund, 2000)
Mounting external debt and large-scale capital flight have been at the forefront of Africa's economic problems since the 1980s. External Debt and Capital Flight in Sub-Saharan Africa, edited by S. Ibi Ajayi and Mohsin S. Khan, takes a penetrating look at debt and capital flight during the 1990s in Ghana, Kenya, Nigeria, Tanzania, and Uganda. The book describes the size and composition of debt in the selected countries and examines the causes of the debt buildup. It also assesses the extent of capital flight and suggests ways of stemming the flight of financial resources.